Pengaruh Kebiasaan Membaca Terhadap Kemampuan Membaca Pemahaman Siswa Kelas V SD Negeri 9 Lhoksukon - Rahmi, Riza; Fitriani, Suci; Safiah, Intan (Universitas Syiah Kuala, 2023)
In learning Indonesian, reading habitual activities that have been carried out by schools have not been embedded in students, students talk more with friends and play when the implementation of reading activities takes place. Most students only read without understanding the content they read, so this reading habit can be seen from their reading ability at school, but students' reading comprehension is still lacking where some students still have difficulty determining the main ideas of paragraphs and re-expressing what they read and vocabulary mastery. owned by low students. Therefore, students who lack interest in reading will find it difficult to understand what they read, this will affect their reading comprehension skills. The formulation of the problem in this study is how does the influence of reading habits on the reading comprehension ability of fifth grade students at SD Negeri 9 Lhoksukon. The purpose of this study was to determine the effect of reading habits on the reading comprehension ability of fifth grade students at SD Negeri 9 Lhoksukon. This research is quantitative and this type of research is correlational. The population in this study were all students in grades I to VI of SD Negeri 9 Lhoksukon totaling 117 students, by taking samples in class V totaling 41 students covering 2 VA classes 22 students and 19 students in VB class. Data collection tools in the form of questionnaires and tests. Data analysis techniques using the t-test at a significant level = 0.05. Data analysis, obtained thtunng ttable = 8.98 2.023. Based on the hypothesis testing criteria, it was found that Ho was rejected and H1 was accepted. So the conclusion in this study is that there is a significant influence of reading habits on the reading comprehension ability of fifth grade students of SD Negeri 9 Lhoksukon is accepted.